Tourist Attractions in Campursari Lyrics: Analysis of Figurative Language and of Meaning - Budi Purnomo; Nunun Tri Widarwati; Arini Hidayah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: Many of Didi Kempot’s campursari songs have the themes of tourist attractions. In the Javanese song lyrics and carry the sadness of a man who lost his lover, they contain various figurative languages and meanings related to the ethics and attitudes of Javanese people in using language in their lives by showing language and figurative languages when talking to certain people at a certain place and at a certain time. However, not many people know the figurative languages and meanings expressed in the lyrics of tourist attraction themed songs. Methodology: The campursari songs with the themes of tourist attractions were first studied. The lyrics taken from the seven songs were analyzed based on Gibbs’ types of figurative language and Leech’s types of meaning. Three expert raters who are fluent in Javanese, Indonesian and English were asked to review the accuracy and clarity. In using content analysis, the primary data were gathered from the Didi Kempot & Sobat Ambyar Orchestra-YouTube video. Findings: The types of figurative language in the lyrics of campursari songs with the themes of tourist attractions are personification, hyperbole, litotes, simile and repetition. The types of meaning contained in the lyrics of campursari songs are conceptual, connotative, social, affective, reflective, collocative and thematic meanings. The meanings related to Javanese ethics and attitudes include the attitudes of narima ‘receptiveness’, sabar ‘patient’, tepa slira ‘tolerance’, aja ngaya ‘don’t push yourself’ and aja srakah ‘don’t be greedy’. Conclusion: The results of this study are expected to make the public better know and understand the figurative languages and of meanings contained in the lyrics of campursari songs with the themes of tourist attractions. Originality: This study attempts to analyze the figurative languages and the meanings of the lyrics of campursari songs with the themes of tourist attractions, as never been previously done, and make the public better know and understand them. This research also intends to analyze the meanings associated with the ethics and attitudes of the Javanese in using figurative languages in their lives. Keywords: tourist attractions; campursari lyrics; figurative language; meaning